MiR-142-5p and miR-486-5p as biomarkers for early detection of chronic antibody-mediated rejection in kidney transplantation. (2nd January 2017) - Iwasaki, Kenta; Yamamoto, Takayuki; Inanaga, Yukiko; Hiramitsu, Takahisa; Miwa, Yuko; Murotani, Kenta; Narumi, Shuji; Watarai, Yoshihiko; Katayama, Akio; Uchida, Kazuharu; Kobayashi, Takaaki
Abstract: De novo donor-specific HLA antibody (DSA) would not necessarily contribute to chronic antibody-mediated rejection (CAMR) in kidney transplantation. Here, we investigated whether PBMC miRNAs could be predictable biomarkers for CAMR. Microarray profiling of 435 mature miRNAs in pooled samples was conducted. Individual analysis revealed that miR-142-5p was significantly ( p  < 0.01) underexpressed in patients with DSA. After DSA production, miR-486-5p and its target PTEN/foxO3 mRNA were significantly overexpressed ( p  < 0.01) and underexpressed ( p  < 0.01), respectively, in patients with biopsy-proven CAMR, compared with non-CAMR. Our studies suggest that miRNA expression patterns may serve as noninvasive diagnostic biomarkers to evaluate immune response and kidney allograft status.